2019
DOI: 10.1002/ijgo.12790
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intertwin interval on short‐term neonatal outcomes of the second twin in dichorionic pregnancies with vaginal delivery

Abstract: Objective To examine the effect of intertwin interval on umbilical cord pH and Apgar scores of the second twin after vaginal delivery. Methods A retrospective study of twin deliveries at a university hospital in Spain between August 2012 and September 2017. Inclusion criteria were vaginal delivery of both twins at 32 gestational weeks or more. Exclusion criteria were monochorionic pregnancies and indication for cesarean delivery. The sample was dichotomized by intertwin interval (<10 and ≥10 minutes). Neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While increasing inter-twin delivery interval has been thought to be associated with adverse outcomes in vaginal births of twins, 38 further studies have suggested that in cases of uncomplicated twin delivery with normal fetal monitoring, the intertwin delivery-time interval is not a predictor of adverse pregnancy outcomes. 39 While decreased umbilical cord arterial pH has been seen in the second twin with increasing delivery-time interval, [38][39][40] and a long interval is associated with higher rates of low Apgar score and an increase in cord lactate, 41 these associations do not translate into higher rates of admission to the neonatal intensive care unit. 42 As most of the deliveries in our study were cesarean deliveries, major differences in delivery-time intervals are not expected or relevant in our population.…”
Section: Discussionmentioning
confidence: 99%
“…While increasing inter-twin delivery interval has been thought to be associated with adverse outcomes in vaginal births of twins, 38 further studies have suggested that in cases of uncomplicated twin delivery with normal fetal monitoring, the intertwin delivery-time interval is not a predictor of adverse pregnancy outcomes. 39 While decreased umbilical cord arterial pH has been seen in the second twin with increasing delivery-time interval, [38][39][40] and a long interval is associated with higher rates of low Apgar score and an increase in cord lactate, 41 these associations do not translate into higher rates of admission to the neonatal intensive care unit. 42 As most of the deliveries in our study were cesarean deliveries, major differences in delivery-time intervals are not expected or relevant in our population.…”
Section: Discussionmentioning
confidence: 99%
“…22,27 Benito et al concluded that second twins delivered after an inter-twin interval exceeding 10 minutes had poorer APGAR scores and higher rates of blood pH <7.15. 28 Current guidance advises that the inter-twin interval should not exceed 30 minutes as this causes poor perinatal outcomes secondary to acute hypoxia due to decreased placental perfusion. 27,29 However, rare cases of extremely delayed inter-delivery intervals up to 131 days have been reported in the interest of delaying extremely premature deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Very strict intertwin intervals of 10 minutes as well as more ease intervals of 30 minutes have been looked at as well [34]. However, a clear de nition of the ideal intertwin interval cannot be deduced from literature.…”
Section: Intertwin Interval Ph and Apgar Scorementioning
confidence: 99%